Global Solidarity on #كل_العيون_على_رفح News Based on Norman Fairclough’s Critical Discourse Analysis - Khonsa, Nabila Nur; Basid, Abdul; Al Anshory, Abdul Muntaqim (Jurnal Bahasa dan Sastra, 2025)
This research examines the discourse of global solidarity in the news surrounding the hashtag #كل_العيون_على_رفح (#AllEyesOnRafah) on Aljazeera Arabic and CNN Arabic news media based on Norman Fairclough's critical discourse analysis. This research uses descriptive qualitative with data in the form of news texts from the official websites of the two media and related literature. The analysis is conducted through three dimensions: textual, discourse, and social practices. The results show that Aljazeera Arabic consistently builds a narrative of global solidarity with Palestine through emotional diction, intensive coverage, and active interactive on social media. This global solidarity is reinforced by the support of international actors and boycott campaigns as digital resistance to Israel. In contrast, CNN Arabic tends to present this phenomenon neutrally, focusing on the balance of information and the effects of the boycott critically. These findings show that global solidarity is not only represented in texts, but also has an impact on the public, social mobilisation, and pressure on global actors.